Aprostocetus azoricus - Nunes, Rui (2021)
JUSTIFICATION: Aprostocetus azoricus is an endemic eulophid wasp species of the Azores (Portugal), having been present at least historically on Flores island. From the historical data, this species had a very small Extent of Occurrence (8 km²) and Area of Occupancy (8 km²). It is possible that this species has declined in the past as a result of human activity, but the present situation of this species needs to be further assessed and further research is needed into its population, distribution, threats, ecology, life history and indigenous host species. Conservation/restoration of native habitats, as well as invasive plant species control, could potentially aid this species' conservation. Based upon the lack of recent data regarding this species population, distribution, threats, ecology and hosts, this species is assessed as Data Deficient (DD).